On the dialogue of values in sacral architecture and art of the east and west - Uścinowicz, Jerzy (Journal of Architecture and Urbanism, 2007)
The author reviews the past and present examples of the diffusion of values in the Christian Churches, i.e., of the Eastern (Orthodox and Unite) and West (Roman Catholic and Protestant). They are portrayed through mutual conversion of temples, incorporation of traditional orthodox iconography in contemporary Roman Catholic churches as well as by adaptation of historic temples for their mutual ecumenical use. The values give testimony to the synthesis of art of both Christian Churches as well as to the return to their ecclesial unity. Apart from a retrospective look at contemporary, post-war buildings of this type the authors’ realizations are also introduced. These examples are representative for the architecture of cultural borderland which attempts to synthesize both the Western and Eastern Christian art. Apie vertybių dialogą rytų ir vakarų sakralinėje architektūroje Santrauka. Analizuojama kultūrų dialogo sakralinėje architektūroje tema. Pasitelkiant istorinius ir šiuolaikinius pavyzdžius aptariamos Rytų (stačiatikių ir unitų) ir Vakarų (katalikų ir protestantų) bažnytinėje architektūroje pasireiškusios tarpusavio įtakos ir sąveikos buvusios Lenkijos Karalystės ir Lietuvos didžiosios kunigaikštystės teritorijoje. Nagrinėjamos maldos namų konfesinės konversijos, jų naudojimas ekumeninėms apeigoms, stačiatikių ikonografijos apraiškos katalikų bažnyčiose. Straipsnio autorius dalijasi krikščioniškojo meno sinteze pagrįstų meninių sprendimų taikymo patirtimi, sukaupta projektuojant maldos namus. Reikšminiai žodžiai: architektūra, šventykla, sakralumas, konversija, adaptacija, sintezė, paribiai. First published online: 21 May 2013